Private Sector Delivery of Rural Piped Water Services in Bangladesh : A Review of Experience, 2003-2015 - World Bank (Washington, DC, 2016)
This note explores the Bangladesh experience in implementing the widespread use of a private operator model for building and operating rural piped water schemes. Since the early 1990s, the World Bank has, through a series of development projects, designed, piloted, and attempted to scale up use of the model as a mechanisms to address the very real issues of arsenic contamination and delivery at scale. The latest of these projects is still in implementation. The experience with these projects to date has been disappointing, and while a limited number of schemes are still in operation, the model has not been replicated in a large number of communities as intended and has not proved to be particularly sustainable. Over this same period, the government and other development partners also have been using alternative methods to deliver the same kinds of services in rural areas. Some of these efforts seem to have been modestly successful. However, much of the evidence about the performance of these other models is anecdotal and there has been little rigorous analysis to compare the performance of these different models with the private sponsor approach. This paper attempts to do this on the basis of a desk review of existing World Bank literature, including project documents and research reports, coupled with interviews with key stakeholders and World Bank staff. The first section of the paper provides an overview of the rationale and key issues associated with efforts to scale up a private operator model in Bangladesh. The second section reviews government efforts and those of its other development partners, to use a more traditional mode of service provision, involving community management. The third, fourth, and fifth sections review efforts by the government and the World Bank to design, test, and scale up a private operator model for service provision. A sixth section reviews some of the international research that provides insights into the use of such models in other countries and sectors. The paper ends with tentative conclusions about the experience in Bangladesh, lessons learned, and several options for further analysis.